(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article covers the methodology for the development of digital competence of students studying in higher education organizations on the basis of multimedia technologies. In addition, the structure of the use of the gamification method in the organization of classes based on multimedia technologies was developed by the authors as an example.